Construction of Hierarchical Porous Architecture on Ni Foam for Efficient Oxygen Evolution Reaction Electrode - Ao, Guang-Hong; Zhao, Pei-Zhi; Peng, Zhi-Gang; Wang, Shuo; Guo, Ying-Shuang; Chen, Chun-Tian; Wang, Zhi-Hong (Frontiers in Materials, 2021)
The nickel foam (NF) with a three-dimensional porous structure plays an important role in a wide variety of applications such as energy storage and conversion, catalysis, and sensor due to its high porosity, low density, and excellent conductivity. However, the main drawback of NF is its ligaments are very smooth and thus the surface area is relatively low. In this work, we propose a novel strategy, oxidization and reduction process, to in situ construct micron/nano pores on the ligaments of the commercial NF to fabricate a typical hierarchical porous architecture. This process is simple and green, avoiding the use of sacrificial materials. Furthermore, MnO2 is coated on the micron/nano porous Ni foam (MPNF) to construct an oxygen evolution reaction (OER) electrode through pulse electrodeposition. The designed MPNF-MnO2 electrode presents enhanced OER electrocatalysis activity with a low overpotential of 363.5 mV at the current density of 10 mA cm-2 in an alkaline solution, which is 66.4 mV lower than that of the NF-MnO2 electrode in the same operating conditions. Furthermore, the porous and wrinkle structures of the MPNF also improve the mechanical integrity of the electrode, resulting in super-long stability.